Plastic antibody for the electrochemical detection of bacterial surfaceproteins - Khan, M. Azizur R. (2017)
This work presents a novel molecularly imprinted polymer (MIP) for the indirect detection of bacteria, by targeting an outer membrane protein on a disposable device. Protein A (PA) was selected for this purpose, as a representative protein of the outer surface of Staphylococcus aureus. The imprinted polymer was assembled directly on a ﬁlm of single walled carbon nanotubes (SWCNTs), placed on screen-printed electrodes (SPEs). The MIP material was produced by electropolymerizing 3-aminophenol in the presence of the protein template (PA) using cyclic voltammetry (CV). The proteins entrapped at the polymeric backbone were digested by the action of proteolytic activity of proteinase K and then washed away to create vacant sites. The performance of the corresponding imprinted and non-imprinted electrodes was evaluated by EIS and the effect of several variables, such as monomer and template concentrations, or thickness of imprint-ing surface, was controlled and optimized by the number of CV cycles. The detection limit of the MIP-based sensors was 0.60 nM in MES buffer. High repeatability and good selectivity were observed in the presence of a model protein BSA. The sensor performance was also tested to check the effect of inorganic ions in tap water. The detection limit observed was 16.83 nM, with a recovery factor of 91.1 ± 6.6%. The sensor described in this work is a potential tool for screening PA on-site, due to the simplicity of fabrication, disposability, short response time, low cost, good sensitivity and selectivity.